Constructing the experience of chronic pain through discourse. (March 2013) - Robinson, Katie; Kennedy, Norelee; Harmon, Dominic
Abstract The aim of this study was to investigate the discourses used by people with chronic pain. Using qualitative interview data from five Irish people with a variety of chronic pain conditions, Foucauldian discourse analysis was undertaken to identify the discourses in operation in participants' accounts. Three discourses were identified: a moral discourse, a discourse of pain as personal tragedy, and a biomedical discourse. A moral discourse was used to construct participants as moral individuals experiencing real pain who try to accomplish activities and fulfil social roles without burdening others. The discourse of chronic pain as personal tragedy describes the multiple negative consequences of chronic pain including activity, relationship, physical, financial, and emotional consequences, and changed expectations of the future. This discourse bolsters the moral discourse through rejecting any benefits associated with chronic pain. Participants rejected a biomedical discourse by proposing their own explanatory models of pain, resisting psychosocial understandings of pain, criticizing medical professionals and healthcare services, and challenging medical expertise, professionalism, and power. These practices allow participants to reject the patient subject-position with its attendant passivity and requirements for adherence and compliance.